Similar improvements in 5‐km performance and maximal oxygen uptake with submaximal and maximal 10‐20‐30 training in runners, but increase in muscle oxidative phosphorylation occur only with maximal effort training - Skovgaard, Casper; Christiansen, Danny; Martínez‐Rodríguez, Alejandro; Bangsbo, Jens (Scandinavian journal of medicine & science in sports, 2024)
Objective The aim of the present study was to examine whether 10‐20‐30 training (consecutive 1‐min intervals consisting of 30 s at low‐speed, 20 s at moderate‐speed, and 10 s at high‐speed), performed with submaximal effort during the 10‐s high‐speed runs, would lead to improved performance as well as increased maximum oxygen uptake (VO2‐max) and muscle oxidative phosphorylation (OXPHOS). In addition, to examine to what extent the effects would compare to 10‐20‐30 running conducted with maximal effort. Design Nineteen males were randomly assigned to 10‐20‐30 running performed with either submaximal (SUBMAX; n = 11) or maximal (MAX; n = 8) effort, which was conducted three times/week for 6 weeks (intervention; INT). Before and after INT, subjects completed a 5‐km running test and a VO2‐max test, and a biopsy was obtained from m. vastus lateralis. Results After compared to before INT, SUBMAX and MAX improved (p < 0.05) 5‐km performance by 3.0% (20.8 ± 0.4 (means±SE) vs. 21.5 ± 0.4 min) and 2.3% (21.2 ± 0.4 vs. 21.6 ± 0.4 min), respectively, and VO2‐max was ~7% higher (p < 0.01) in both SUBMAX (57.0 ± 1.3 vs. 53.5 ± 1.1 mL/min/kg) and MAX (57.8 ± 1.2 vs. 53.7 ± 0.9 mL/min/kg), with no difference in the changes between groups. In SUBMAX, muscle OXPHOS was unchanged, whereas in MAX, muscle OXPHOS subunits (I‐IV) and total OXPHOS (5.5 ± 0.3 vs 4.7 ± 0.3 A.U.) were 9%–29% higher (p < 0.05) after compared to before INT. Conclusion Conducting 10‐20‐30 training with a non‐maximal effort during the 10‐s high‐speed runs is as efficient in improving 5‐km performance and VO2‐max as maximal effort exercise, whereas increase in muscle OXPHOS occur only when the 10‐s high‐speed runs are performed with maximal effort.